Brachytherapy in the therapy of prostate cancer – an interesting choice - Skowronek, Janusz (Contemporary Oncology/Współczesna Onkologia, 2013)
Brachytherapy is a curative alternative to radical prostatectomy or external beam radiation [i.e. 3D conformal external beam radiation therapy (CRT), intensity-modulated radiation therapy (IMRT)] with comparable long-term survival and biochemical control and the most favorable toxicity. HDR brachytherapy (HDR-BT) in treatment of prostate cancer is most frequently used together with external beam radiation therapy (EBRT) as a boost (increasing the treatment dose precisely to the tumor). In the early stages of the disease (low, sometimes intermediate risk group), HDR-BT is more often used as monotherapy. There are no significant differences in treatment results (overall survival rate – OS, local recurrence rate – LC) between radical prostatectomy, EBRT and HDR-BT. Low-dose-rate brachytherapy (LDR-BT) is a radiation method that has been known for several years in treatment of localized prostate cancer. The LDR-BT is applied as a monotherapy and also used along with EBRT as a boost. It is used as a sole radical treatment modality, but not as a palliative treatment. The use of brachytherapy as monotherapy in treatment of prostate cancer enables many patients to keep their sexual functions in order and causes a lower rate of urinary incontinence. Due to progress in medical and technical knowledge in brachytherapy (“real-time” computer planning systems, new radioisotopes and remote afterloading systems), it has been possible to make treatment time significantly shorter in comparison with other methods. This also enables better protection of healthy organs in the pelvis. The aim of this publication is to describe both brachytherapy methods.